Love - Eswaran, Vijay, Dato'; VStudios ([S.l.] : VStudios, 2008)
Dato' Vijay Eswaran delivers yet another thought-provoking message when he talks about love saying, the single and the most powerful motivating force in the universe. In social networking,when team that build with love, nobody can tear it apart
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing